(3TQM GdebGeGJ (B/s - (3GdReNTQj, eMehO Hf YeQ Hf eMeO,s 467-538 (3gLQjs; (3GdaGQhbj, eMeO SYjOs; (3GdReNTQj, eMehO Hf YeQ Hf eMeO,s 467-538 (3gLQjs; (3GdReNTQj, eMehO Hf YeQ Hf eMeO,s 467-538 (3gLQjs ((3OeTb (B:s (3OGQ GdfhGOQ,s, 2013)
(3COH GdebGeGJ(B.s
(3WHY gPG GdcJGH Yf GdWHYI GdCUdjI GdeYJeOI hGdeWHhYI Yf GdWHYI GdYHGSjI(B.s
Keywords: (3GdebGeGJ GdYQHjIs -- (3JGQjN hfbOs -- (3GdYUQ GdYHGSj, (B750-1258s